Redeeming Thucydides' Book VIII : narrative artistry in the account of the Ionian War - Liotsakis, Vasileios (De Gruyter, 2017)
Since antiquity, Book 8 of Thucydides' History has been considered an unpolished draft which lacks revision. Even those who admit that the book has some elements of internal coherence believe that Thucydides, if death had not prevented him, would have improved many chapters or even the whole structure of the book. Consequently, while the first seven books of the History have been well examined through the last two centuries, the narrative plan of Book 8 remains an obscure subject, as we do not possess an extensive and detailed presentation of its whole narrative design. Vasileios Liotsakis tries to satisfy this central desideratum of the Thucydidean scholarship by offering a thorough description of the compositional plan, which, in his opinion, Thucydides put into effect in the last 109 chapters of his work. His study elaborates on the structural parts of the book, their details, and the various techniques through which Thucydides composed his narration in order to reach the internal cohesion of these chapters as well as their close connection to the rest of the History. Liotsakis offers us an original approach not only of Book 8 but also of the whole work, since his observations reshape our overall view of the History.
Keywords: Thucydides. -- History of the Peloponnesian War. -- Book 8.; History of the Peloponnesian War (Thucydides); Thucydides -- ca. 460 v. Chr.-400 v. Chr.; Thucydides -- ca. 460 v. Chr.-400 v. Chr. -- Historiae -- 8; Historiography.; Greece -- History -- Peloponnesian War, 431-404 B.C.; Grèce -- Histoire -- 431-404 av. J.-C. (Guerre du Péloponnèse); Historiographie.; historiography.; HISTORY -- Ancient -- Greece.; Historiography; Greece; Erzähltechnik; 431-404 B.C.; (Produktform)Electronic book text; (Zielgruppe)Fachpublikum/ Wissenschaft; (BISAC Subject Heading)LIT004190; (BISAC Subject Heading)HIS002000: HIS002000 HISTORY / Ancient / General; (BIC subject category)DSBB: Literary studies: classical, early & medieval; (BIC subject category)HBLA: Ancient history: to c 500 CE; Historiography; Peloponnesian War; Thucydides; EBK: eBook; (VLB-WN)9553; History